Water and nutrients recovery from synthetic source-separated human urine using AGMD. Issue 2 (April 2022) - Yao, Hong; Hu, Zhifeng; Qing, Weihua; Sun, Shaobin; Zhang, Wen
Abstract: Human urine is one of the largest nutrient contributors to the municipal wastewater's nutrient load, which, if not properly managed, may cause severe eutrophication in natural waters. Reclaiming the nutrients from source-separated urine could potentially substitute 20–25% of commercial fertilizers and save up to 30% of the energy consumption for biological nutrient removal. The present study investigated the performances of urine separation and water recovery using air gap membrane distillation (AGMD), which recovers water via vapor conversion and transfer across the membrane and concentrates urine salts. The effects of operation conditions (e.g., the temperatures and flow rates of feed and coolant) on water permeate flux were examined. The results show that a high permeate flux (~14 L·m −2 ·h −1 ) and a low specific ammonia transfer (< 0.1 g·L −1 ) were achieved under optimal operations of the feed flow rate and the temperatures. Increasing feed flow or cold coolant flow or the thermal gradients can substantially increase permeate flux. Moreover, the Stefan diffusion model was used to compare and validate the experimental observations. The actual operational parameters and membrane properties (e.g., feed/coolant temperatures, air gap thickness, and membrane thickness) were employed in the model calculation without any fitting or unknown parameters. The modeling and experimental results matched well and highlights the promising potential of this model for guiding the design and operation of this AGDM process for urine separation and water recovery. Graphical Abstract: Synopsis : AGMD was employed for the first time to separate water from human urine to reduce the nutrient load on wastewater treatment plants and reclaim nutrients and water for onsite usage such as fertilizer, irrigation, and toilet flushing. ga1 Highlights: A high permeate flux (14 LMH) was achieved in AGMD for water recovery from source-separated urine. Experimental and modeling analysis indicates the permeate flux depends on flow rates and temperatures. Variations of the total ammonia concentrations or pH do not significantly vary the permeate flux. Hydrolyzed urine or high pH increases the co-transfer of ammonia gas with water vapor.